Sustainable Tourism Village Development in Sidoarjo through the Pentahelix Model and Geospatial Planning - Sri Iriani; Muhammad Husain; Syaifurizal Putra; Farid Pribadi; Yessy Artanti; Muhammad Rahmadhan; Dwiarko Nugrohoseno; Dewie Wardoyo; Inggrit Hasanah; Yustina Crismardani (Environment and Social Psychology, 2026)
This paper analyses the application of the Pentahelix approach in Sidoarjo’s tourism village development, highlighting the importance of joint actions among key stakeholders to realise SDG 8, SDG 11, and SDG 17. The research adopted a descriptive qualitative strategy that integrated document analysis, field interviews, and group discussions, targeting stakeholders selected through purposive sampling. Data analysis was conducted using thematic coding to identify patterns in stakeholder participation, challenges, and best practices. Findings indicate that Pentahelix collaboration has positively impacted infrastructure improvements, marketing strategies, and tourism management practices, creating opportunities for local economic growth and cultural preservation. However, the study also identifies gaps, particularly in the involvement of academic institutions in research and innovation, and limited community participation in decision making processes. Strengthening the participatory capacity of local communities and enhancing cross sector cooperation can lead to more equitable benefits, foster a stronger sense of ownership, and support long term sustainability. The research provides practical implications for policymakers and tourism practitioners seeking to implement integrated, community based development models, suggesting that sustained dialogue, capacity building programs, and monitoring mechanisms are essential to maximize the potential of Pentahelix partnerships. Overall, this study contributes to the literature on collaborative governance in rural tourism and highlights the importance of multi stakeholder engagement for sustainable and inclusive village development.